2021
DOI: 10.1111/jfpp.15361
|View full text |Cite
|
Sign up to set email alerts
|

Using a red‐fleshed and six varieties of thinned young apple to make juice and their phytochemicals characterization

Abstract: Finding an environmentally friendly way to utilize thinned young apple (TYA) fruits is of great interest in food industry since they were found rich in functional phytochemicals. Making TYA juice is an excellent way but very limited knowledge has been acquired. The juice‐making procedures optimization of a red‐fleshed and six varieties of TYA fruits were performed with/without steam sterilization before juicing, and the color index, phytochemicals particularly including phenolics and aromas were detailed chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The volatile compounds in PAJ and FAJ samples were determined by a Headspace Solid-Phase Microextraction coupled with Gas Chromatography-Mass Spectrometer (HS-SPME-GC/MS) method described by Yang et al ( 23 ) with certain modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The volatile compounds in PAJ and FAJ samples were determined by a Headspace Solid-Phase Microextraction coupled with Gas Chromatography-Mass Spectrometer (HS-SPME-GC/MS) method described by Yang et al ( 23 ) with certain modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The volatile compounds in fermentation samples were analyzed by a Headspace Solid-Phase Microextraction coupled with Gas Chromatography-Mass Spectrometer (HS-SPME-GC/MS) method described by Yang et al ( 18 ) with certain modifications.…”
Section: Methodsmentioning
confidence: 99%
“…In another recent study, Yang et al 68 studied the impact of steam sterilization (at 100 °C for 15 minutes under atmospheric pressure) of thinned young RFA before juice-making procedures. Results showed that steaming sterilization led to color stability and maintenance, higher sugar contents, and comparable acid contents, but a lower juice yield and lower total (poly)phenol content in the treated juices (33% (poly)phenols less compared to untreated juices).…”
Section: Effect Of Technological Processing On Red-fleshed Apple (Pol...mentioning
confidence: 99%
“…In another recent study, Yang et al 68 studied the impact of steam sterilization (at 100 °C for 15 minutes under atmospheric pressure) of thinned young RFA before juice-making…”
Section: Effect Of Technological Processing On Red-fleshed Apple ( Po...mentioning
confidence: 99%